Participatory environmental governance and climate change adaptation: mainstreaming of tidal river management in South-West Bangladesh - Haque, Kazi Nurmohammad Hossainul; Chowdhury, Faiz Ahmed; Khatun, Kazi Rabeya (Springer India, 2016)
This article was published in Land and Disaster Management Strategies in Asia [ © 2015 Springer India ] and the definite version is available at: https://doi.org/10.1007/978-81-322-1976-7_13 The book chapter's website is at: http://link.springer.com/chapter/10.1007%2F978-81-322-1976-7_13